Demokrasi Bukan Untuk PKI: Pengeklusian Hak-Hak Politik Kaum Komunis Pasca Reformasi di Indonesia - Zuhdan, Muhammad (ijd-demos, 2019)
This study wants to review the exclusion of the political rights of communist-leaning community groups to exercise their political rights in Indonesia. Political rights agreed here start from the agreed right, the right to organize, until the right to hold an election to take part in the general election. The author's thesis says that the 15 years of Reformation failed in Indonesia because there was still the exclusion of the political rights of people accused of being PKI henchmen in democratic life in Indonesia. The purpose of this paper in academia is to erase the participation of the inclusion and exclusion discourse of ex-PKI political prisoners joining the political and governance system in Indonesia. Another aim was to advocate for the exclusion of the political rights of groups or people accused of being PKI henchmen. The focus of this paper is to analyze the practice and forms of exclusion of the political rights of the Pki ex-politics and to save in socio-political life in Indonesia. After reading this paper, it will discuss the democratic ironism that developed in Indonesia after the 1998 Reformation because it still opens opportunities for exclusion of the political rights of a minority group.Â Penelitian ini ingin mengulas pengeklusian hak-hak politik kelompok masyarakat berhaluan komunis untuk menggunakan hak politiknya di Indonesia. Hak politik yang dimaksud disini mulai dari hak menyatakan pendapat, hak berorganisasi, sampai hak mendirikan partai sampai ikut dalam pemilihan umum (Pemilu) . Tesis penulis mengatakan bahwa 15 tahun Reformasi gagal di Indonesia karena masih ada pengeklusian hak politik Â orang-orang yang dituduh antek PKI dalam kehidupan berdemokrasi di Indonesia. Tujuan tulisan ini secara akademis untuk membongkar perdebatan wacana inklusi dan ekslusi eks Tapol PKI beserta keluarganya dalam sistem politik dan pemerintahan di Indonesia. Tujuan lainnya adalah untuk mengadvokasi pengeklusian hak-hak politik kelompok ataupun orang-orang yang dituduh antek PKI. Fokus tulisan ini adalah menganalis praktek dan bentuk ekslusi atas hak-hak politik eks tahanan politik Pki dan keluarganya dalam kehidupan sosial politik di Indonesia. Setelah membaca paper ini pembaca akan memahami tentang ironisme demokrasi yang berkembang di Indonesia pasca Reformasi 1998 karena masih membuka peluang ekslusi atas hak-hak politik sebuah kelompok minoritas.